One-eyed science: occupational health and women workers - Messing, Karen (Philadelphia, 1998)
"After decades of research by the author and her colleagues into what women do in positions such as bank teller, secretary, waitress, nurse, factory worker, and poultry processor, Karen Messing is astonished to find that for many policymakers, researchers, and activists, the topic of women's occupational health doesn't exist. Messing investigates different types of occupational health issues for women, notably the controversial topics of male/female differences in jobs, health, and basic biology. The pain and suffering of women workers is illustrated in vivid case studies of research into health risks for women in the workplace, including musculoskeletal disease, the hazards of office work, emotional stress, and reproductive hazards. No longer can employers, administrators, and health professionals ignore the very real problems women encounter in their jobs. Throughout the book, Messing captures the everyday reality of workplace tasks and stresses-from lifting boxes to juggling mental tasks under pressure to the emotional labor of caring for upset or abusive people- by combining on-site observing with listening to the workers' descriptions of their work lives. Responding to the tough question, why are scientists so unresponsive to the needs of women workers, Messing describes long-standing difficulties in gaining attention for the occupational health of women, ranging from the structure of the grant process and the conferences crucial to the professional life of researchers to the basic assumptions of scientific practice. Messing laments the separation of even most feminist health researchers from workplace concerns and asserts that it is time to develop a science that can prevent women workers' pain and suffering. "